Proyecto de factibilidad para la creación de una empresa dedicada a la elaboración y comercialización de cofres mortuorios en la ciudad de Loja. - Amay Ortiz, Ángel Medardo (2012)
The present research concerns the implementation of a company dedicated to the development and commercialization of mortuary chests in the city of Loja, because there is the raw material required and necessary labor. To determine the feasibility of the project began with a study of market, size and location, project engineering, business organization and financial evaluation In a market study it was determined the effective demand for the use of mortuary chests for the first year is 98% which represents us 1780 which is suitable for implementing the company. The investment required to operate in fixed assets is $ 3,761.47, in deferred assets are $ 700.00y working capital is $ 6211.19 giving a resulting total investment of $ 10,672.66, it will be funded 37.48% which represents the sum of $ 4,000.00 by the bank of Loja and equity is $ 6672.66 with a percentage of 62.52%. The sales revenue budget for the first year of mortuary chests will be $ 89,260.43, cash flow for the first year shows an amount of $ 7,579.27. The results obtained in the financial evaluation indicators, demonstrate the feasibility of the investment, with an NPV of 23216.98y a Cup of Return of 78.89% Capital Recovery Period is 4 months and go28days; Costode1 benefit , 22 is that for every dollar invested will have a utility of 0.22 cents and the sensitivity analysis indicates that the project resists increased costs of 14.46% and a decrease in revenues of 11.85%, to launch the enterprise thereby contributing to economic development of the city of Loja. It has also established its legal and administrative organization with a legal identification of Limited Liability Company, also established different hierarchical levels and functions to be performed by each of the persons to serve on the company. This as such is structured, it is anticipated that the project life is a period of five years, being located in the city of Loja. With the implementation of the project shows that it is feasible to have all the resources, it should be noted that the product has market acceptance is inevitable to make good publicity, in order to achieve spreading characteristics, considering the analysis demand, supply and levels of marketing this product, also shows that in this project, the sensitivity values are less than one, therefore do not affect changes in project costs and increased revenue, ice the project is not sensitive to these changes, finally to the implementation of this project is recommended from the financial point of view, as evidenced by their respective indices evaluation.